A novel radiographic method to facilitate measurement of the tibial plateau angle in dogs - Headrick, J.; Cook, J.; Helphrey, M.; Crouch, D.; Fox, D.; Schultz, L.; Cook, C.; Kunkel, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
The tibial plateau levelling osteotomy (TPLO) is commonly performed for treatment of cranial cruciate ligament deficiency in dogs. In order to be performed as described, this procedure relies on consistent measurement of the tibial plateau angle (TPA) on radiographs. This prospective study compared two radiographic methods for subsequent TPA measurement with respect to measured angle and ease of determining landmarks for measurement as determined by four observers. One method was the accepted standard radiographic protocol outlined in the TPLO training seminars. The other method involved a novel split image radiographic protocol not yet described in the literature. Participants' subjective scores as to ease of identifying landmarks and determining TPA on radiographs for each method were evaluated. Inter-observer TPA measurement variability was also assessed for each method. The novel radiographic method was judged to be significantly better in terms of ease of measuring TPA. Inter-observer measurement variability was considered appropriate for recommending use of this novel method for radiographing patients for TPA measurements.
Keywords: TPA; TPLO; radiographic methods; canine